2018
DOI: 10.1016/j.jtcvs.2017.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Bovine arch anatomy influences recoarctation rates in the era of the extended end-to-end anastomosis

Abstract: Arch anatomy often goes undocumented on preoperative imaging, yet children undergoing extended end-to-end repair with bovine arch anatomy are at a significantly increased risk of recoarctation. This may be due to a reduced clampable distance to facilitate repair. These results should be considered in the preoperative assessment, parental counseling, and surgical approach for children with discrete aortic coarctation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…There have been several studies evaluating risk factors for adverse outcomes after surgical intervention, including recoarctation, although the literature is often conflicting and inconclusive, especially regarding the influence of child weight and surgical strategy on the rate of reinterventions [7,8,13,14]. Other possible risk factors identified in individual studies include anatomical and morphological characteristics of the aortic arch, preoperative care, and age at time of the intervention [12,14,15]. Nevertheless, a comprehensive analysis of the evidence to determine the risk factors conclusively lacks in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies evaluating risk factors for adverse outcomes after surgical intervention, including recoarctation, although the literature is often conflicting and inconclusive, especially regarding the influence of child weight and surgical strategy on the rate of reinterventions [7,8,13,14]. Other possible risk factors identified in individual studies include anatomical and morphological characteristics of the aortic arch, preoperative care, and age at time of the intervention [12,14,15]. Nevertheless, a comprehensive analysis of the evidence to determine the risk factors conclusively lacks in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]8,[10][11][12][13]16 The results of our analysis of indicated that bovine arch is not associated with fetal anomalies, although we appreciate that our study was underpowered. The bovine arch pattern has been described in the pediatric literature as associated with coarctation of the aorta, 19 and higher rates of prevalence have been reported in pediatric populations with congenital disease (17.6% among patients with aortic coarctation compared to 15.2% in the entire population studied). 20 The low percentage of congenital heart disease in our study population made the sample underpowered to assess such a relationship.…”
Section: Discussionmentioning
confidence: 95%
“…While we did not include presence of bovine arch, or measures between brachiocephalic vessels in our analysis, Turek et al noted that these are important predictive factors for reintervention; 28.6% of their patients with a bovine arch had a postoperative gradient of 20 mm Hg or greater. 15 We plan to incorporate this as well as other arch characteristics in our future study.…”
Section: Commentmentioning
confidence: 99%